THE INFLUENCE OF THE TYPE OF BLADE MATERIAL IN THE BANANA STICK WASTE SHREDDING MACHINE ON THE QUALITY OF THE CHIPPED PRODUCTS - Yamin, Muhammad; Joharsah; Rasyid, Muksin (Journal of Science Technology (JoSTec), 2024)
The banana gedebog waste chopper machine moves mechanically so that it cuts with a blade, the mechanical analysis of the machine consists of a chopper mechanism. For the analysis of choppers that use the main components, namely blades and shafts, while the driving mechanism is a supporting component such as electric motors, pulleys, and bearings. In analyzing the chopping machine aims to analyze the mechanical work of power and analyze the steps of each component work, analyze the results of the type of material usage of the blade. The driving engine power used is 94.57363 (watts) and the chopping force is 4.51375 x 10-6 (kg.m). The variation of rotation on the drive motor produces a variation of rotation on the chopping knife which has an average of good quality with the largest amount if using used blade material per car.